The Correlation Between Feeding Patterns and the Incidence of Wasting Among Toddlers in Tempurejo District, Kediri - Nanda Putri Aprilia; Oktovina Rizky Indrasari (Ficco Scientific Corner, 2025)
Background: Wasting is a form of acute malnutrition measured by the weight-for-height (WFH) or weight-for-length (WFL) index, commonly caused by inadequate feeding patterns. This study aimed to analyze the correlation between feeding patterns and the incidence of wasting in toddlers in Tempurejo District, Kediri. Methods: This study used a quantitative approach with a cross-sectional design. The sampling method was non-probability purposive sampling, and there were 178 respondents. The data used were primary data collected through questionnaires, and the data were analyzed using SPSS with a chi-square test. Results: Most of the children in this study are boys (55,1%), aged 36 to 59 months (53,9%), and have improper eating habits (57,9%). Wasting was found in 28,1% of the children, with the highest occurrence among boys (58%) and those aged 36 to 59 months (50%). The bivariate analysis showed a correlation between feeding patterns and the occurrence of wasting (p-value 0,017). Conclusions: There is a significant association between feeding patterns and the incidence of wasting.